2017
DOI: 10.1371/journal.pone.0173403
|View full text |Cite
|
Sign up to set email alerts
|

Does gamification increase engagement with online programs? A systematic review

Abstract: BackgroundEngagement in online programs is difficult to maintain. Gamification is the recent trend that offers to increase engagement through the inclusion of game-like features like points and badges, in non-game contexts. This review will answer the following question, ‘Are gamification strategies effective in increasing engagement in online programs?’MethodEight databases (Web of Science, PsycINFO, Medline, INSPEC, ERIC, Cochrane Library, Business Source Complete and ACM Digital Library) were searched from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
160
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(193 citation statements)
references
References 29 publications
4
160
0
12
Order By: Relevance
“…The study found a significant main effect of game elements on the amount of user generated tags, with the control condition being significantly outperformed by the points condition, and the points condition being significantly outperformed by both the leaderboards and levels condition (Mekler et al, 2015). This finding, coupled with Looyestyn's discussion of the effective use of leaderboards (Looyestyn et al, 2017), strongly supports the idea that rewards and more complex reward mechanics are able to increase user engagement in many gamified contexts.…”
Section: Common Video Game Rewardssupporting
confidence: 53%
See 1 more Smart Citation
“…The study found a significant main effect of game elements on the amount of user generated tags, with the control condition being significantly outperformed by the points condition, and the points condition being significantly outperformed by both the leaderboards and levels condition (Mekler et al, 2015). This finding, coupled with Looyestyn's discussion of the effective use of leaderboards (Looyestyn et al, 2017), strongly supports the idea that rewards and more complex reward mechanics are able to increase user engagement in many gamified contexts.…”
Section: Common Video Game Rewardssupporting
confidence: 53%
“…In 2017, Looyestyn et al, undertook a systemic review of gamification as an engagement intervention for online programs (Looyestyn, et al, 2017). The researchers examined 15 papers on gamification in online programs, and concluded that gamification is an effective means of increasing engagement in that context.…”
Section: Video Game Rewards In Gamificationmentioning
confidence: 99%
“…Basta con hacerse estas preguntas y diseñar luego la solución en torno a la respuesta. Las tablas de clasificación, por su parte, al organizar jugadores por rango, son una forma particularmente útil de aumentar el compromiso de los usuarios (Looyestyn et al, 2017).…”
Section: Explicar El Valor De Los Puntos Y Nivelesunclassified
“…Sin embargo, la influencia positiva de la ludificación sobre el grado de compromiso de los usuarios parece disminuir con el tiempo. Su eficacia tiene un efecto temporal dado que el atractivo de las recompensas tiende a desvanecerse con el tiempo, una vez superado el período de novedad o primicia, que puede ser breve (Looyestyn et al, 2017).…”
Section: Inconvenientes Y Peligrosunclassified
“…Gamification refers to the process of using game mechanics to enhance user engagement and problem solving . This often takes the form of multimedia educational platforms such as online question banks or smartphone applications, and are interactive in nature .…”
Section: Introductionmentioning
confidence: 99%